About Safe Loads of Cables with Cross-Linked Polyethylene Insulation - V. N. Radkevich; R. V. Romanov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
Permissible long currents of cables with voltage 6-lOkV and cross-linked polyethylene insulation are considered in the paper. Smoothing functions have been obtained to estimate permissible long densities of the current in three- and single-core cables at various types of a lining and an arrangement. It is shown that in the field of large section conductors permissible values of current densities in heating can be less than economic ones.